Education tools for entrepreneurship - Peris-Ortiz, Marta; Alonso Gómez, Jaime; Vélez Torres, Francisco (Springer, 2016)
Entrepreneurship in all of its aspects, connotations and applications has undoubtedly become a major force for new and sustainable wealth creation not only in emerging but also in developed economies. The challenge consists in how to inspire or work beyond the mental limits in the classroom, to determine which learning platforms are required or useful to unlock and stimulate creativity and to eliminate the human aversion to failure. Can educators teach entrepreneurship? Can universities teach that failure may be a necessary part of this process? Is the education or the conditions created in the surrounding environment the key factor? Is there an entrepreneurial education tool or methodology that could help stu- dents to develop an entrepreneurial attitude or mind-set? This book confirms that education is a positive response to all of these questions. This force is indeed opening new possibilities for individuals which transcend all generations and lifestyles, new ways to foster development across industries as well as new innovation and entrepreneurial ecologies that help to develop robust socio- economical communities, such as those in Boston, Massachusetts; the Silicon Valley in California; Monterrey, Mexico; the Basque Country in Spain; and obvi- ously many additional examples. In this context, this book is a joint effort by a group of professors and academic institutions from both sides of the Atlantic Ocean, Mexico, Spain and Portugal, which introduce this entrepreneurial mind-set into both the traditional face-to-face classroom and the emerging “virtual” classroom: as expected, the aim is to imple- ment “new intellectual wealth” and new enriched and enhanced methodologies and tools to the learning dynamics which students undertake in their academic careers. In my capacity as an entrepreneur for more than 30 years and also as chairman of the Board of Trustees of CETYS University in Mexico (one of the participating universities in this book), I see tremendous potential and I especially celebrate this entrepreneurial approach to education as a crucial factor in developing agents of vi change, new wealth creation, robust socio-economic development and ultimately, societal prosperity and peace. The potential outcome is vitally important when seeking the methodology which will liberate the creative and practical aspects of development. Are the tools and methods the same in all cultures? It is an intellectual delight to observe the entrepreneurship dynamics in our teaching-learning process and the high-level involvement of professors, students and mentors-coaches from many areas of human activity (NGOs, businesses, civil associations) in order to provide new relevant, rigorous and robust entrepreneurship- based learning. This book on “Education Tools for Entrepreneurship” is a tribute to the profes- sors and academic institutions which envision entrepreneurship and innovation as a new driving force for global education and development.
Keywords: Education; Entrepreneurship; Campus Tijuana